Alcohol Brands Being Socially Responsible on Social Media? When and How Warning Conspicuity and Warning Integration Decrease the Efficacy of Alcohol Brand Posts among Under-Drinking-Age Youth. Issue 2 (3rd May 2020) - Lou, Chen; Alhabash, Saleem
Abstract: While federal regulations and alcohol industry self-regulation have been exhorting alcohol advertisers to include warnings, such as legal drinking age, on alcohol advertisements, it is rare to see this practice on social media. This study investigated the effects of warning conspicuity and warning-ad claim integration on under-drinking-age youth's reactions to beer brand posts on social media (i.e., Instagram) and explicated the underlying mechanisms. The findings demonstrate that large-sized warnings (versus small-sized warnings) and integrated warnings (versus nonintegrated warnings) attract more visual attention, respectively. When warnings are integrated to the focal claims of the brand posts, a big-sized warning evokes greater state reactance than a small-sized one. However, when the warning is separated from the claim, a small-sized warning triggers higher reactance than a big-sized one. Underage participants' state reactance mediates the interaction effect of warning conspicuity and warning integration on brand attitudes and intentions to interact with the brand posts, which in turn affect their intentions to drink alcohol, respectively.